LEGAL PROTECTION OF DEBTORS ON FINANCING AGREEMENTS WITH FIDUCIARY GUARANTEES IN THE FORM OF MOTORIZED VEHICLES - Nurlaily Nurlaily (Universitas Gorontalo, 2022)
Transferring a motor vehicle as a fiduciary guarantee to a third party may not be carried out by the debtor without written approval from the creditor. This debtor's actions can be categorized as embezzlement, so the validity of the existence of motorized vehicles as fiduciary guarantees in the financing agreement will be questioned. The researcher used a normative legal research method with a conceptual and statutory approach in this study. The results showed that in Batam, the rights transfer of the motor vehicle guarantee from the first debtor to the second debtor was carried out by directly handing over the motor vehicle using a private agreement. The transfer is only allowed if there is permission from the finance company. The second debtor who has good faith gets the transfer of the rights from the first debtor by making installment payments until it is paid off to the finance company. When the payments are fully paid, the legal protection given to the debtor for the motor vehicle will end after the first debtor performs Roya (abolition of the mortgage) and submits proof of ownership of the motor vehicle to the second debtor, who has good intentions in fulfilling the creditor's receivables.